A Study of the Internal Structure of the Anchor Personality Inventory [Kajian Struktur Internal dari Anchor Personality Inventory] - Riyono, Bagus (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2020)
The Anchor Personality Inventory (API) is based on the Anchor personality theory. The objective of this study is to perform a comparative analysis between the internal structures of API and Big Five Personality. The data was collected from 333 students from a university of various faculties. The data analysis to examine the structure of API was an exploratory factor analysis. The result of the study shows that the API constructs fall into different factors, separated from the Big Five Personality constructs. Virtues is the strongest construct of API, followed by material, self, and others. Anchor Personality Inventory (API) merupakan konstruksi alat ukur kepribadian menurut teori kepribadian anchor. Tujuan dari penelitian ini adalah untuk membandingkan struktur internal konstruk dari API dengan konstruk kepribadian berdasarkan teori Big Five Personality. Subjek penelitian terdiri dari 333 mahasiswa satu perguruan tinggi dari berbagai fakultas. Teknik analisis data untuk menguji struktur dari konstruk penyusun API adalah analisis faktor eksploratori. Hasil analisis faktor menunjukkan bahwa keempat konstruksi anchor memiliki loading factor yang terpisah dari lima konstruksi kepribadian Big Five Personality. Virtues adalah konstruksi terkuat di antara empat anchor, diikuti oleh materi, self, dan others.